Effects of Dispersion and Charge‐Transfer Interactions on Structures of Heavy Chalcogenide Compounds: A Quantum Chemical Case Study for (Et2Bi)2Te. Issue 4 (23rd February 2022) - van der Vight, Felix; Schulz, Stephan; Jansen, Georg
Abstract: The reasons for the unusually small Bi−Te−Bi bond angle of 86.6° observed in the crystal strucure of (Et2 Bi)2 Te are investigated by quantum chemical calculations. With the help of coupled cluster theory at the CCSD(T) level it is demonstrated that the structure of an isolated monomer should have a bond angle larger than 90°, despite a Bi−Bi distance in good agreement with the value of 4.09 Å found in the crystal structure. The discrepancy is resolved by a lengthening of the Bi−Te bond in the crystal, which is shown to be caused by partial electron transfer from neighbouring molecules to the Bi−Te σ * orbital. Through symmetry‐adapted perturbation theory at the DFT‐SAPT level it is shown that London dispersion interactions are highly important for the packing of molecules in the solid state and, in turn, for the small Bi−Te−Bi bond angle. Abstract : Through quantum chemical calculations it is shown that the unusually small Bi−Te−Bi bond angle of 86.6° in the crystal structure of (Et2 Bi)2 Te stems from a combination of intermolecular charge transfer and dispersion interactions.